Retreatment of Chronic Hepatitis C Infection with Telaprevir: Preliminary Results in Turkey - Orhan Yıldız (Balkan Medical Journal, 2015)
Background: The use of pegylated interferon alpha and ribavirin (PegIFN/RBV) for the retreatment of chronic hepatitis C virus (HCV) infection without a sustained virological response (SVR) prior to PegIFN/RBV treatment has resulted in low success rates.